(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
This research presents a comparative analysis in managing process of three incubators located in Tlaxcala and Aguascalientes. Through a study quantitative, non-experimental, transversal and comparative, with an instrument of 45 questions which key informants were the directors of the centers of incubation. The results show that differences exits and so does the number of companies incubated is much higher in Tlaxcala that in Aguascalientes. It was concluded that the comparison reveals that both have the number of incubated projects.